The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 6th International Conference on Electronic Commerce - ICEC '04 2004
DOI: 10.1145/1052220.1052292
|View full text |Cite
|
Sign up to set email alerts
|

Emerging customer trends towards mobile music services

Abstract: Elaborating on the rapid evolution of mobile entertainment services, this paper investigates customers' preferences and attitudes towards mobile music services in Europe through an exploratory research approach. The study ran in Finland, United Kingdom and Greece, targeting both music consumers and music professionals. Significant differences were observed between the three countries in terms of the importance music consumers attach to specific mobile music buying criteria and functionalities. Music consumers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Previous research has also reported that there are differences in music consumer behavior in different countries. In (Vlachos et al, 2004), this has been found to occur in the criteria people use when selecting mobile music services and rating the importance of their functionalities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has also reported that there are differences in music consumer behavior in different countries. In (Vlachos et al, 2004), this has been found to occur in the criteria people use when selecting mobile music services and rating the importance of their functionalities.…”
Section: Discussionmentioning
confidence: 99%
“…The Vlachos and Vrechopoulos [2004] study suggests that there are no big differences in buying criteria between music professionals, that is, people who work in the generic music industry value chain, and those of music consumers; the mobile music service requirements are almost identical for both. The most important buying criterion for music professionals and consumers is content (i.e., "good sound/image quality" and "variety of music songs/video clips") [Vlachos and Vrechopoulos 2004].…”
Section: Two Significant Buying Decisionsmentioning
confidence: 96%
“…Studies that have addressed mobile music phenomena usually fall into two categories: surveys and statistics that rely on selfreporting and sales records [5,10], and ethnography using qualitative methods such as interviews [6,9]. For instance, Synovate Ltd. [5] recently probed interests for new kind of music services from 8000 respondents around the globe.…”
Section: Previous Researchmentioning
confidence: 99%